2017
DOI: 10.17122/ogbus-2017-2-63-79
|View full text |Cite
|
Sign up to set email alerts
|

Technology of Application of Crosslinked Polymeric Compositions

Abstract: Северо-Покурского месторождения.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Trivalent metal salts act as cross-linkers in this technology: when they interact with the carboxyl group of the polymer, a cross-linked spatial structure is formed that prevents water filtration [ 83 ] ( Figure 18 ).…”
Section: Gels For Conformance Control and Flow Diversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trivalent metal salts act as cross-linkers in this technology: when they interact with the carboxyl group of the polymer, a cross-linked spatial structure is formed that prevents water filtration [ 83 ] ( Figure 18 ).…”
Section: Gels For Conformance Control and Flow Diversionmentioning
confidence: 99%
“…Due to the adjustable cross-linking time and the transition of the polymer solution into the gel, it is possible to place the gel screen at a predetermined distance from the injection well in such a way that, by changing the direction of the water flow, it leads to the displacement of oil from the bypassed parts of the reservoir (Figure 17). Trivalent metal salts act as cross-linkers in this technology: when they interact with the carboxyl group of the polymer, a cross-linked spatial structure is formed that prevents water filtration [83] (Figure 18). Trivalent metal salts act as cross-linkers in this technology: when they interact with the carboxyl group of the polymer, a cross-linked spatial structure is formed that prevents water filtration [83] (Figure 18).…”
Section: Gels Based On Acrylamide Polymersmentioning
confidence: 99%
“…Studies have shown that viscoelastic systems capable of generating normal stresses are one of the most effective buffer systems for cementing, since they are able to displace drilling fluid even from pinched zones [3,4]. However, it remains a challenge to design the compositions of these systems without detailed knowledge of their behaviour under various loads.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies using the described polymer compositions have proven to be a reliable method for isolating highly permeable reservoir intervals in order to prevent water and gas breakthrough into production wells (Gumerova & Yarkeyeva 2017).…”
Section: Introductionmentioning
confidence: 99%